2016
DOI: 10.1002/ptr.5653
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological Review of Bioactive Constituents ofPaeonia lactifloraPallas andPaeonia veitchiiLynch

Abstract: The roots of two peony species, Paeonia lactiflora Pallas and Paeonia veitchii Lynch are routinely referred to as either chishao () or baishao (). This paper reviews the botanical origins and traditional medicinal usage of each species, as well as pharmacological like activity of their constituents. A search of herbal pharmacological encyclopaedia, PubChem and PubMed databases identified their known constituents. The biological data for these constituents were evaluated and classified according to pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 179 publications
(209 reference statements)
1
81
0
3
Order By: Relevance
“…Polyphenolic compounds from plant extracts possess many beneficial properties; including antiviral activities (Hsu, 2015; Parker et al, 2016; Yang et al, 2016). In this study, we have explored the in vitro antiviral capacity of different polyphenols, and shown that EGC, EGCG, and D inhibit WNV infection, and that the last two also inhibit DENV and ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenolic compounds from plant extracts possess many beneficial properties; including antiviral activities (Hsu, 2015; Parker et al, 2016; Yang et al, 2016). In this study, we have explored the in vitro antiviral capacity of different polyphenols, and shown that EGC, EGCG, and D inhibit WNV infection, and that the last two also inhibit DENV and ZIKV.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniae Radix Rubra (RPR, Chishao) is the naturally dried root of P. lactiflora Pall. or Paeonia veitchii Lynch (Parker et al, ). In Japanese Pharmacopoeia, Paeoniae Radix is described as the root of P. lactiflora Pall.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibited inflammatory pain via modulation of N‐methyl‐D‐aspartate in the brain cortex and reduced related cytokines, such as tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, IL‐6, IL‐10, IL‐12, and IL‐17 (Dai et al, ; Sun et al, ; Xu et al, ). Paeoniflorin upregulated apoptosis of MGC‐803 human gastric carcinoma cells and HT29 human colorectal cancer cells (Chen, Lee, et al, ; Parker et al, ; Zheng et al, ). It inhibited proliferation, invasion, and metastasis of MCF‐7/MDA‐MB‐231 human breast cancer cells and human A549 lung cancer cells (Parker et al, ; Zhang, Yuan, Cui, Xiao, & Jiang, ; Zhou, Wang, Song, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E: antioxidante, antimicrobiano, inmunomodulador, anticáncer, antitusivo, antiinflamatorio, protector cardiovascular (Hou & Jin 2012;, antinefrítico, antidiabético, hipoglucémico, hipolipidémico (Jia et al 2003;Wang et al 2015), hepatoprotector (Lu et al 2014), anti-obesidad , prebiótico (Shi et al 2015), hematopoyético (Fleischer et al 2016), antiosteoporosis , antitrombótico (Kou et al 2006), neuroprotector , ansiolítico (Lin & Zhao 2015), sedante, anti-insomnio , anti-fatiga (Chen et al . 2010 E: antioxidante, antiinflamatorio, inmunomodulador, antiviral, antibacteriano, hipoglucémico, protector cardiovascular, antiarterioesclerótico, anti-obesidad hipolipidémico (He & Dai 2011;Zhang et al 2015;Parker et al 2016), anticáncer (Lam et al 2015), antitrombótico (Ye et al2016), hematopoyético , antidermatósico , neuroprotector (Fu et al 2015; anticonceptivo (Zhang et al 2016), antidepresivo (Farahani et al 2015), anti-amenorrea (Arentz et al 2015), relajante uterino (Hehir & Morrison 2016), potenciador sexual: disfunción eréctil, hiperplasia prostática, androgénico (Washida et al 2009;Hetchman 2013). Perilla frutescens (L.) Britton Lamiaceae China, Corea, Japón, Taiwán, Bután, India, Sudeste asiático Zi su, shiso…”
Section: Colocasia Esculenta (L) Schott Araceae China Taiwán Yu Tarunclassified